PENGARUH KEAHLIAN, PENGALAMAN AUDITOR, DAN SKEPTISME PROFESIONAL TERHADAP PEMBERIAN OPINI OLEH AUDITOR (STUDI EMPIRIS PADA KANTOR AKUNTAN PUBLIK DI WILAYAH KOTA BEKASI DAN DKI JAKARTA) - Anggitarahma, Pingka Pamulia; Maidani, Maidani; Eprianto, Idel (LPPM Institut Pendidikan Nusantara Global, 2024)
The purpose of this study is to test and analyze the effect of expertise, experience, and professional skepricism on giving opinions by auditors. This research method uses quantitative research methods, with the type and source of data, namely primary data obtained through distributing questionnaires to public accounting firms in the Bekasi City and DKI Jakarta areas. The population and sample of this study is the total number of auditors who work in public accounting firms in the Bekasi City and DKI Jakarta areas. The sampling technique used was purposive sampling technique and resulted in a total of 86 processed date samples that met the criteria. The analytical methods used are descriptive statistical tests, validity and reliability tests, classical assumption tests, regression tests with multiple linear regression, analysis of the coefficient of determination (R2 / R Square), and hypothesis testing. The results of this study show that expertise has no influence on giving opinions by auditors, auditor experience have a possitive effect oh giving opinions by auditors, and professional skepticism have a possitive effect on giving opinions by auditors.